Body length and occipitofrontal circumference may be good indicators of neurodevelopment in very low birthweight infants – secondary publication. (22nd February 2018) - Watanabe, Yoshitaka; Itabashi, Kazuo; Taki, Motohiro; Miyazawa, Tokuo; Nakano, Yuya; Murase, Masahiko
Abstract: Aim: The aim of this study was to predict the neurological prognosis of very low birthweight (VLBW) infants. We examined the relationship between nutritional status, brain volume measured by magnetic resonance imaging (MRI) and anthropometric measurements of VLBW infants at term‐equivalent age (TEA). Methods: We evaluated 27 VLBW infants, born at Showa University Hospital in Japan between April 2012 and August 2013, who underwent brain MRI at TEA. Based on their clinical data, we analysed their protein and energy intake. Results: Median values for the 27 VLBW infants were as follows: gestational age, 29.7 weeks; birthweight 1117 g; protein intake 2.7 g/kg/day and energy intake 97.9 kcal/kg/day. At TEA, the standard deviation scores (SDSs) of body weight, body length and the occipitofrontal circumference (OFC) were −0.8, −1.4 and 0.7, respectively. Multiple regression analysis revealed that the SDSs of body length and the OFC at TEA were significant determinants of white matter volume, but that the SDS of body weight at TEA was not. Conclusion: Our findings suggest that the SDSs of body length and the OFC at TEA may be better indicators than body weight for predicting the development of the central nervous system in VLBW infants receiving nutritional management.